Causes of infective endocarditis in the Western Cape, South Africa: a prospective cohort study using a set protocol for organism detection and central decision making by an endocarditis team - Anton Frans Doubell; Hans Prozesky; Jantjie Taljaard; Jacques Janson; Alfonso Jan Kemp Pecoraro; Colette Pienaar; Philippus George Herbst; Simon Poerstamper; Lloyd Joubert; Mae Newton-Foot (BMJ Open)
Background Blood culture negative infective endocarditis (BCNIE) poses both a diagnostic and therapeutic challenge. High rates of BCNIE reported in South Africa have been attributed to antibiotic use prior to blood culture sampling.Objectives To assess the impact of a systematic approach to organism detection and identify the causes of infective endocarditis (IE), in particular causes of BCNIE.Design Prospective cohort study.Methods The Tygerberg Endocarditis Cohort study prospectively enrolled patients with IE between November 2019 and February 2021. A set protocol for organism detection with management of patients by an endocarditis team was employed. This prospective cohort was compared with a retrospective cohort of patients with IE admitted between January 2017 and December 2018.Results One hundred and forty patients with IE were included, with 75 and 65 patients in the retrospective and prospective cohorts, respectively. Baseline demographic characteristics were similar with a mean age of 39.6 years and male predominance (male sex=67.1%). The rate of BCNIE was lower in the prospective group (28/65 or 43.1%) compared with the retrospective group (47/75 or 62.7%; p=0.039). The BCNIE in-hospital mortality rate in the retrospective cohort was 23.4% compared with 14.2% in the prospective cohort (p=0.35). A cause was identified (including non-culture techniques) in 86.2% of patients in the prospective cohort, with Staphylococcus aureus (26.2%), Bartonella species (20%) and the viridans streptococci (15.3%) being most common.Conclusion The introduction of a set protocol for organism detection, managed by an endocarditis team, has identified Staphylococcusaureus as the most common cause of IE and identified non-culturable organisms, in particular Bartonella quintana, as an important cause of BCNIE. A reduction in in-hospital mortality in patients with BCNIE was observed, but did not reach statistical significance.